PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR - Mawardah, Qori; Rambe, Riris Nurkholidah (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The aim of this research is to produce picture story book media that is valid, practical and effective for students of the Syifaurrahma Islamic Education Foundation in improving their reading skills. This type of research uses development research (R&D), which is adapted from the ADDIE model which consists of analysis, design, development, implementation and evaluation. The research subjects were 3rd grade students of the Syifaurrahma Islamic Education Foundation consisting of 9 male students and 13 female students. The research instruments used were interviews, media expert validation sheets, material experts, post-test, pre-test, teacher response questionnaire, and student response questionnaire. The data analysis technique used is quantitative and qualitative data analysis. This data is data related to validation and responses from media expert lecturers, material experts, teacher responses, and student responses regarding the picture story books being developed. The percentage of results from experts regarding the picture story book media received very valid and practical criteria with scores of 93% (material experts), 100% (media experts), 95% (teacher response questionnaire) and 95% (student response questionnaire). The effectiveness test results obtained from the pretest experienced significant changes and received an N-gain value of 0.83, so it can be concluded that the picture story book media category is very feasible, practical and effective for use in improving students' reading abilities.